A partial map of the circular mitochondrial genome of Drosophila melanogaster. Location of EcoRI-sensitive sites and the adenine-thymine- rich region (The Rockefeller University Press, 1976)
The mitochondrial genome of Drosophila melanogaster is a circular DNA molecule of mol wt 12.35 X 10(6) daltons. A single region accounting for approx. 25% of this molecule can be reproducibly differentially denatured presumably because it is rich in adenine and thymine. We have mapped on the circular mitochondrial genome of D. melanogaster the relative positions of this adenine-thymine (A-T) rich region and the sites sensitive to cleavage by the restriction endonuclease EcoRI, using agarose gel electrophoresis and electron microscopy. Digestion of mitochondrial DNA (mtDNA) molecules to completion with EcoRI resulted in the production of four fragments, A, B, C, and D which represent (+/- SD) 58.9 +/- 1.1%, 27.5 +/- 0.8%, 8.9 +/- 0.5%, and 4.5 +/- 0.3%, of the circular genome length, respectively. Fragments produced by EcoRI digestion and circularized by incubation at 2 degrees C also fell into four distinct length groups with means (+/- SD) of 59.1 +/- 0.5%, 27.5 +/- 0.5%, 9.2 +/- 0.3%, and 4.6 +/- 0.2% of the circular genome length. From a consideration of the lengths of fragments resulting from incomplete EcoRI digestion, it was determined that the arrangement of the fragments in the circular genome was A-C-B-D. By electron microscope examination of partially denatured EcoRI fragments, the A-T- rich region was shown to be located in the A fragment closer to one end than to the other. By similar partial-denaturation studies of fragments resulting from incomplete EcoRI digestion, it was determined that, in the circular genome, of the two EcoRI sites which define the limits of the A fragment, the site between the A and D fragment lies nearest to the A-T-rich region.